Play Store Data Scrapping and Preprocessing done as Sentiment Analysis Material - Hasanah, Rakyatul; Sulistiani, Sulistiani; Nurhikmayani, Nurhikmayani; Hasanah, Zakiyah; Wijaya, Setiawan Ardi; Abdennasser, Dahmani; Sharkawy, Abdel Nasser (CV. Abhinaya Indo Group, 2025)
Sentiment analysis is a computational technique used to interpret user opinions about a product through textual reviews. This research aims to prepare useful data for further research, one of which is sentiment analysis. A total of 12000 recent reviews from July 2024 - January 2025 were collected through web scrapping. The research process includes data preprocessing steps such as case folding and data cleaning to transform the raw data into a usable format. The raw data up to the given changes have been uploaded to the mendeley data repository to be reprocessed into further research, one of which is the sentiment analysis approach.